Repositioning Islamic Religious Education in the National Curriculum: A Philosophical Critique of the Teacher Ordinance Legacy - Husnul Haetami; Ahyar Ahyar; Saparudin Saparudin (Sekolah Tinggi Agama Islam Sadra, 2026)
The positioning of Islamic Religious Education within Indonesia’s national curriculum cannot be adequately understood without examining the epistemological legacy of colonial educational policy. During the Dutch colonial period, regulations such as the Teacher Ordinance of 1905 and its 1925 revision, along with the Wild School Ordinance of 1932, were introduced to regulate and control Islamic teaching and indigenous educational institutions. Beyond administrative control, these policies established a regulatory logic that shaped the authority, legitimacy, and scope of Islamic knowledge within the educational system. This study offers a philosophical critique of the Teacher Ordinance legacy by analyzing how its underlying logic continues to influence the epistemological position of PAI in contemporary Indonesian education. Employing a qualitative library-based method, the analysis proceeds through historical-textual examination, philosophical interpretation using a power–knowledge framework, and normative-conceptual reconstruction. The findings demonstrate that colonial policy produced an enduring epistemic structure characterized by the bureaucratic regulation of teachers, the hierarchical classification of knowledge, and the subordination of religious education to secular-rational standards. These structures persist in transformed forms within the national curriculum, contributing to the marginal epistemological position of PAI. From the perspective of Islamic philosophy of education, this condition reflects a disjunction between the integrative conception of knowledge (‘ilm) and the fragmented logic of modern curriculum design. This study argues that the problem is not merely institutional but epistemological, and proposes a philosophical repositioning of PAI as an integrative and foundational component of the Indonesian national education system.